The effect of concept cartoon-embedded worksheets on grade 9 students' conceptual understanding of Newton's Laws of Motion. Issue 1 (2nd January 2017) - Atasoy, Şengül; Ergin, Serap
Abstract: Background: A substantial review study of concept cartoons reports that few studies have indicated their functions. For this reason, the present study illuminates the extent to which concept cartoon-embedded worksheets (through constructivist context) accomplish these functions in conceptual learning. Purpose: The purpose of the study is to determine the effect of the concept cartoon-embedded worksheets on grade 9 students' conceptual understanding of Newton's Laws of Motion. Sample: Within a quasi-experimental research design with control group, the sample consisted of 102 grade 9 students (aged 15–16 years) enrolled in an Anatolian High School. They were randomly assigned to control (52 students) and experimental groups (50 students). Design and methods: While the control group followed the existing physics instruction, the experimental one was exposed to the concept cartoon-embedded worksheets. To collect data, two scales (Newton's Laws of Motion Test –NLMT– and Interview about Instances –IAI) were employed. Results: The results indicated that the experimental group performed better than did the control group. Conclusions: It can be deduced that the concept cartoon-embedded worksheets are effective in improving grade 9 students' conceptual understanding and in replacing their alternative conceptions with scientific ones.